AtLa1 protein initiates IRES‐dependent translation of WUSCHEL mRNA and regulates the stem cell homeostasis of Arabidopsis in response to environmental hazards. (23rd April 2015) - Cui, Yuchao; Rao, Shaofei; Chang, Beibei; Wang, Xiaoshuang; Zhang, Kaidian; Hou, Xueliang; Zhu, Xueyi; Wu, Haijun; Tian, Zhaoxia; Zhao, Zhong; Yang, Chengwei; Huang, Tao
Abstract Plant stem cells are hypersensitive to environmental hazards throughout their life cycle, but the mechanism by which plants safeguard stem cell homeostasis in response to environmental hazards is largely unknown. The homeodomain transcription factor WUSCHEL (WUS) protein maintains the stem cell pool in the shoot apical meristem of Arabidopsis. Here, we demonstrate that the translation of WUS mRNA is directed by an internal ribosomal entry site (IRES) located in the 5′‐untranslated region. The AtLa1 protein, an RNA‐binding factor, binds to the 5′‐untranslated region and initiates the IRES‐dependent translation of WUS mRNA. Knockdown of AtLa1 expression represses the WUS IRES‐dependent translation and leads to the arrest of growth and development. The AtLa1 protein is mainly located in the nucleoplasm. However, environmental hazards promote the nuclear‐to‐cytoplasmic translocation of the AtLa1 protein, which further enhances the IRES‐dependent translation of WUS mRNA. Genetic evidence indicates that the WUS protein increases the tolerance of the shoot apical meristem to environmental hazards. Based on these results, we conclude that the stem cell niche in Arabidopsis copes with environmental hazards by enhancing the IRES‐dependent translation of WUS mRNA under the control of the AtLa1 protein.